Deformation and Stress Status of a Cable-Stayed Bridge Revealed by Incorporating Ascending-Descending Time Series Interferometric SAR Fusion and Finite Element Modeling - Lianhuan Wei; Shiliu Wang; Xiaotian Wang; Qingbo Ma; Xiaoqiong Qin; Meng Ao; Xin Li; Dong Zhao; Cristiano Tolomei (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Time series interferometric synthetic aperture radar (TS-InSAR) is a noncontact active satellite observation technology that has gradually revealed its potential in bridge deformation monitoring with unprecedented point density and accuracy. Similarly, the finite element modeling (FEM) has also been conducted to analyze deformation and stress distribution of bridge structures, estimating the structural health status. However, previous studies typically utilized sparse in-situ deformation measurements, which only capture the stress of the main components, making it difficult to obtain the local distribution. To address this issue, this study proposes a method that incorporates high-resolution ascending-descending TS-InSAR fusion measurements with FEM, improving the bridge deformation and stress distribution analysis. Taking a cable-stayed bridge as an example, the structural deformation is extracted from ascending TerraSAR-X and descending COSMO-SkyMed SAR images, serving as a constraint for stress state analysis. The experimental results show that the area most significantly affected by temperature deformation are located at both ends of the main bridge, with the maximum longitudinal thermal deformation rates of −0.71 and 0.88 mm/°C, respectively. Moreover, the TS-InSAR measurements are highly consistent with the FEM simulations. When the ambient temperature rises from 16.5 to 25.0 °C, the maximum longitudinal deformation observed by TS-InSAR differs from the FEM simulation results by less than 1 mm. Furthermore, by inputting the vertical deformation of the bridge obtained from TS-InSAR into the FEM, the stress distribution of the bridge has been calculated, revealing that the critical stress points and potential hazardous sections of the cable-stayed bridge are primarily concentrated at the pier supports, tower-beam connections, cable boundaries, and cable-beam intersections.